Repurchase intention and customer satisfaction in e-commerce application - Vaisal Malik Nasmizal; Astri Yuza Sari (Universitas Negeri Padang, 2022)
This study aims to analyze the repurchase intention of the Pegipegi e-commerce application with satisfaction as a mediating variable. The research sample amounted to 130 respondents. The data is processed using Smart PLS 3.0. The results of the study are: (1) confirmation (ECT) has a positive and significant effect on post-purchase, (2) post-purchase has a positive and significant effect on satisfaction, (3) confirmation (ECT) has a positive and significant effect on satisfaction, (4) post-purchase positive and significant effect on repurchase intention, (5) satisfaction has a positive and significant effect on repurchase intention, (6) post-purchase has a positive and significant effect on repurchase intention through satisfaction.